2015
DOI: 10.1016/j.breast.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic, clinical, and health-related factors associated with breast reconstruction – A nationwide cohort study

Abstract: Keywords:Breast reconstruction Breast cancer Surgery Mastectomy Information given Socio-demographic factors a b s t r a c tWe collected registry-and questionnaire-based data on socio-economic and health status, tumor-and treatment-related variables, and explored associations with receipt of reconstruction and information about treatment options in a nationwide cohort of Danish women, treated for primary breast cancer.A total of 594 women were available for analysis, 240 (40%) of these received reconstruction.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Australian treatment choice results were similar to international findings, with women living in deprived areas having reduced odds of surgery and radiotherapy [ 86 ], breast reconstruction surgery [ 88 , 89 ] and higher rates of non-conservative surgery [ 90 ] and mastectomies [ 86 ]. Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Australian treatment choice results were similar to international findings, with women living in deprived areas having reduced odds of surgery and radiotherapy [ 86 ], breast reconstruction surgery [ 88 , 89 ] and higher rates of non-conservative surgery [ 90 ] and mastectomies [ 86 ]. Fig.…”
Section: Discussionsupporting
confidence: 64%
“…There are many other studies that seek to define socio‐economic variable that affects surgical choice and disease‐related outcomes Our findings on income are in line with other studies that show lower income is associated with lower rates of reconstruction. In particular, the 2015 study by Bodilsen demonstrated that higher income was associated with higher rates of reconstruction among Danish women with free and equal access to health care.…”
Section: Procedures Costs and Health Care Utilizationsupporting
confidence: 89%
“…The results of univariate analysis indicate that unmarried patients younger than 40 years with BMI ≤ 24 kg/m 2 , early‐stage noninvasive lesions, and bilateral nipple/skin‐sparing mastectomies and without neoadjuvant chemotherapy are more likely to opt for implant‐based than autologous IPBR. Surprisingly, the economic status and residency display little influence on the decision, despite they significantly affect the receipt of breast reconstruction . The family history of breast or ovarian cancer, an independent predictor of contralateral prophylactic mastectomy, also demonstrates nonsignificant association with the decision on type of IPBR.…”
Section: Discussionmentioning
confidence: 94%